2007
DOI: 10.1073/pnas.0611005104
|View full text |Cite
|
Sign up to set email alerts
|

A genetic network for the clock of Neurospora crassa

Abstract: A diverse array of organisms from bacteria to humans may have evolved the ability to tell time in the presence or absence of external environmental cues. In the lowly bread mould, Neurospora crassa, biomolecular reactions involving the white-collar-1 (wc-1), white-collar-2 (wc-2), and frequency (frq) genes and their products constitute building blocks of a biological clock. Here we use genetic network models to explain quantitatively, from a systems perspective, how these building blocks interact, and how a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
146
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(160 citation statements)
references
References 32 publications
13
146
0
1
Order By: Relevance
“…When the model in Eq. 3 is linearized, it then becomes similar to the repressilator43. This fact suggested that the coupling of cells might be taken to be similar to that of coupled repressilators42.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When the model in Eq. 3 is linearized, it then becomes similar to the repressilator43. This fact suggested that the coupling of cells might be taken to be similar to that of coupled repressilators42.…”
Section: Resultsmentioning
confidence: 98%
“…2B over time). They analyzed this measure in the context of a system of coupled repressilators related to our own working clock network43. What was missing from this measure is accounting for the between droplet variability in our experiment.…”
Section: Resultsmentioning
confidence: 99%
“…With lights staying on, other events are initiated (e.g., VVD production) and unique lights-on feedback would be enacted. A complex set of biochemical/genetic feedback mechanisms occur in the presence of light (Yu et al, 2007), and thus it is not surprising that we see complex waveforms while lights are on. If entrainment has occurred, then once released into free-running conditions the phase of the free-running cycle should correspond to that of the entrained cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Model Validation, Parameter Estimation, and SimulationsTo validate the model and perform parameter estimation, we used a Monte Carlo-based approach, using the Metropolis algorithm to fit the model to the experimental data (23,24). A full description of the Monte Carlo optimization method can be found in the supplemental materials.…”
Section: Development and Use Of Icue2 To Measure Camp Dynamics-mentioning
confidence: 99%